2022
DOI: 10.1900/rds.2022.18.34
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life and Domain-specific Associated Factors among Patients with Type2 Diabetes Mellitus in South India

Abstract: OBJECTIVE: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder that has a major impact on health-related quality of life (HRQOL). The economic burden of the disease, along with its complications, negatively impact the individual, family, and society of Indian diabetic patients. This study explored the perception of the diabetic HRQOL of South Indian type2diabetic patients. METHODS: This study was a cross-sectional descriptive quantitative study conducted in a tertiary care hospital in Chennai, Tam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…These cytokines are known to play an important role in one of the primary symptoms of complex dengue fever. Further, DM has been discovered to have negative effects on the immune system, such as reduced chemotaxis, leukocyte adhesion, and infection phagocytosis making a person more susceptible to infection [ [7] , [8] , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%
“…These cytokines are known to play an important role in one of the primary symptoms of complex dengue fever. Further, DM has been discovered to have negative effects on the immune system, such as reduced chemotaxis, leukocyte adhesion, and infection phagocytosis making a person more susceptible to infection [ [7] , [8] , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%
“…When examining domain-wise QoL findings from other studies, it was observed that general health, financial worries, and diet satisfaction were the domains predominantly affecting QoL, while Role Limitation due to Physical Health and Physical Endurance were associated with a better QoL score [ 22 ]. Another study revealed that domains like energy mobility, social burden, anxiety, and worry were significant indicators of poor QoL [ 23 ]. These differences again may be attributed to the use of different assessment tools.…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 33 34 ] Diabetes itself is a debilitating condition that affects the overall QOL when compared to nondiabetics. [ 35 36 37 38 ] With added musculoskeletal comorbidities, the QOL is expected to worsen.…”
Section: Discussionmentioning
confidence: 99%